Enhancement of spiders’ population through habitat management in rice (Oryza sativa) fields - TANWAR, R K; GARG, D K; SINGH, S P; DHANDAPANI, A; BAMBAWALE, O M (The Indian Journal of Agricultural Sciences, 2011)
Spiders constitute over 90% of the natural enemy population in rice fields which play important role to contain the insect pests. Due to indiscriminate use of insecticides their population is adversely affected. Hence, there is a need to develop technology for conservation of spiders. In the present study, field trials were conducted in rice for two consecutive years, 2006 and 2007 at Atterna (Sonipat-Haryana) with ‘Pusa Sugandh 4’ (‘Pusa 1121’) for conservation of spiders using straw bundles and planting of other suitable crop on border to increase crop diversity. The experiment included five treatments, ie straw bundles+maize (T1), straw bundles+sunn hemp (T2), straw bundles+Sesbania (T3), only straw bundles (T4) and control (T5) without any interventions. Each plot was of 0.5 acre in size. The straw bundles were placed in sorghum field for 15 days for charging with spiders before use in rice. In rice, these bundles were fixed vertically with bamboo sticks after 15 days of rice transplanting @ 20 bundles/ha so that the lower portion of the bundle remained 15 cm above the water level. The observation made on charging of the straw bundle indicated that each bundle contained 30–40 spider adults, 8–10 spider egg masses, 500–600 spiderlings and 20–30 earwigs. All the treatments (T1 to T4) had significantly lower stem borer and leaf folder as compared to control in both the years. The progressive populations build-up of spiders during the entire crop season indicated only one peak, ie the maximum spider population in September. Spider population on paddy plants remained significantly higher in T1 to T4 as compared to control. On the plant, the maximum spiders remained confined to lower part of the plant (up to 25 cm above the ground). Species composition of different spiders prevailing in paddy crop has also been discussed in the paper.